Population and Sustainable Development A Contextual Debate - Singh, Arun Kumar (National Geographical Journal of India, 2022)
An unprecedented population growth, economic development and environmental change are the hallmanes of the last century. Two billion people have been added in the last 25 years and the world population has moved from 5.3 billion in 1990 to 7.3 billion in 2015. Three countries (China, India and the USA) account for 40 percent of the world population. Startling fact is that the gap between India and China has squeezed and the gap between India and the USA has widened. India with 2.4 percent of the land and more than one sixth of the world population is all set to surpass China by 2030. India is one of the fastest growing economies in the world and the changing consumption pattern of natural resources like air, water and soil has jeopardized our natural habitat and there is a need to address the issue on sustainable basis taking into account indigenous knowledge and expertise. Looking at these issues, the paper is organised into four sections. First section is introductory dealing with the population issues at different scales with India in focus. Second section highlights the population growth and consequent environmental issues. The third section initiates the debate relating to population-environment-development interface and the focus shifting from environmental conservation to human well-being and the last section deals with constitutional bases of sustainable development and operational model for implementation of India's population policy at grass root level. The analyses based on secondary data, international and national reports